Research on flow field characteristic of close-coupled gas atomizing nozzles - BAN Wei; CHEN Jiaqi; LIU Lulu; GE Tao; ZHANG Shuai (Fenmo yejin jishu)
The atomization nozzle is the core component for the metal powder preparation by close-coupled gas atomization method. The pressure at the tip of the melt delivery tube and the stagnation point is very important for the smooth outflow of the molten metal during the atomization process. When the tip of the melt delivery tube is positive pressure, the molten metal cannot flow out of the nozzle smoothly, and in severe cases, it may cause the back spray of the molten metal. The greater the pressure at the stagnation point, the greater the impact force of the atomized gas acting on the molten metal flowing out of the melt delivery tube, and the better the crushing effect. The effects of atomization pressure, protrusion length, and cone-apex angle on the pressure at the tip of the melt delivery tube and the stagnation point were studied by mathematical modeling, experimental verification, and numerical simulation in this paper. The results show that, with the increase of atomization pressure, the length of the negative pressure area remains basically unchanged, while the pressure at the stagnation point increases. With the increase of the melt delivery tube elongation, the length of the negative pressure area increases and the pressure at the stagnation point decreases. With the increase of the cone-apex angle of the melt delivery tube, the pressure at the tip of tube changes from the negative to the positive, resulting in the failure of atomization.